Regenerative Medicine Therapies for Osteoarthritis and Cartilage (Asian Journal of Pharmaceutics (AJP), 2022)
Osteoarthritis (OA) has a high burden and impact on society as it affects the quality of life of both young and olderpatients. OA is a degenerative joint disease characterized by the degeneration of articular cartilage. This cartilageis an avascular, unique matrix composed of chondrocyte cells, which can resist compression and redistribute loadsbut have poor self-regenerative capacity. Numerous types of treatment are available, such as non-pharmacologytreatments involving diet, physiotherapy, exercise, and pharmacological which include different types of drugs.None of these two types has proven to be the ideal treatment, only symptomatic treatment. Total knee replacementis the final and only treatment available and used only when the other types of treatment fails. The intra-articularinjection is an alternative treatment for OA, due to the localized nature of the disease. Various types of bloodproducts are currently used, including platelet-rich plasma and orthokine to alert the inflammation response andenhance the healing process. Recently, regenerative treatments have widely been introduced to overcome thelimitations of current treatments. Mesenchymal Stromal Cells (MSCs), which can differentiate into chondrocytes,are used to regenerate articular cartilage. In addition, the improvements in tissue engineering technology such asthe use of different types of the scaffold as well as blood product and growth factors with MSC have had a greatimpact in treating OA and regenerating cartilage. This review will discuss the pathogenesis of OA and describesthe current clinical management to treat the OA.